Pengenalan Permainan Catur Sebagai Upaya Meningkatkan Kemampuan Daya Ingat Pada Anak Usia 5-6 Tahun - Dewi, Sasa Sandra; Fitriani, Yulianti; Arzaqi, Roby Naufal (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2025)
This research was motivated by the phenomenon of children increasingly engaging in gadgets and screen-based activities, which may negatively impact their development in the future. Therefore, this study focuses on introducing chess as an effort to improve memory skills in early childhood. The aim of this research is to explore how the introduction of chess to young children can enhance their memory abilities. This study employed Classroom Action Research (CAR) conducted in two cycles, involving children aged 5–6 years as the subjects. Data collection techniques included observation, tests, interviews, and documentation, which were analyzed using a qualitative approach through data reduction, data presentation, and conclusion drawing. The results showed that children's memory abilities improved by 80.16%, categorized as Very Well Developed (BSB). These findings indicate that introducing chess is effective for use in early childhood education. The results are recommended as a reference for teachers, schools, and future researchers in developing strategies to support cognitive development in early childhood.